Experience and Perspective: Population Administration Services in Delta City - Bahlamar, Ahmad Riyadh Umar (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2024)
Policy implementation is an important indicator that has a major influence on the success of policies related to public issues. This study aims to analyze and explain the implementation of population administration service policies in Sidoarjo Regency. The basic concept used is Edwards III's policy implementation theory. This qualitative research uses a purposive sampling technique. Data were collected using interviews, observation, and documentation. Data analysis used interactive Miles, Huberman, and Saldana. The research results show that population administration service policies in Sidoarjo Regency have demonstrated adequate quality, but still require innovation and development to increase reliability, speed and management innovation. In Tulangan District, there are obstacles in communication due to the lack of service flow boards and inconsistencies in service times. Meanwhile in Porong District, population administration requirements are good with competent officers, clear service flow boards, and high consistency of service times. Human resources in Porong District are considered good and fast, while in Tulangan District they are quite good. Regarding disposition, both sub-districts provide services according to the needs of their residents. However, regarding the bureaucratic structure, Tulangan District has good SOPs, while Porong District experiences problems in the unclear distribution of the main tasks and functions of village officials.